PERFORMANCE ANALYSIS OF ALTERNATIVE COVERINGS FOR COOLING TOWERS IN BRAZILIAN CAPITALS THROUGH NUMERICAL MODELING - Tomás, A. C. C.; Souza, P. H.; Primo, A. R. M. (Revista de Engenharia Térmica, 2017)
A cooling tower is a heat removal device used to transfer waste heat to the atmosphere process. Today, commercial cooling towers use plastic coverings, specially developed for this application. It is known that alternative coverings have been an increasingly viable solution thanks to its performance and cost. The purpose of this study was to evaluate, through numerical simulation, the performance of different alternative coverings under different climatic conditions. Therefore, we used, as reference, the climate of the state capitals and their respective geographic regions. The performance of these coverings was evaluated through observation of three parameters: effectiveness, approach and cooling. The main input data used by the software EES (Engineering Equation Solver) for the calculation of evaluation parameters were: experimental NUT of each covering, average local temperature, local air pressure and relative humidity. The flow of water and air were set at 0.33 L / s and 170 L / s, respectively. We concluded that the air inlet temperature and relative humidity at each location greatly influence the performance of the coverings. The alternative covering that showed the best results was the "cross-fiber and neck", with an efficiency about 35% lower than the industrial covering. The Brazilian capital city with the best performances for alternative coverings was Palmas (TO). This is due to the very low relative humidity found in the city in the summer. Air humidity is also responsible for the poor performance of coverings in the capitals of the North. In general, the region with the best performance was the South, due to the characteristics of the sub-tropical climate. Regions that had the worst results were North / Northeast because of the weather that combines high temperatures with high / moderate humidity, respectively. Thus, the study of climate conditions is indispensable for the operation prevision of a cooling tower. Alternative coverings will be viable depending on the location.